Bidirectional Impact of Type 2 Diabetes Mellitus and Chronic Periodontitis: A Comparative Study on Inflammatory Biomarkers and Glycemic Control Post-Non-Surgical Periodontal Therapy - Ansari, Salman Tarique; O. Alazmi, Saad; Hafiz Khan, Sabahat; N Gaikwad, Rahul; Nagpal, Deepak (Journal of Neonatal Surgery, 2025)
Background: Periodontitis and Type 2 Diabetes Mellitus (T2DM) are chronic inflammatory diseases that exhibit a bidirectional relationship, with each condition exacerbating the other. This study evaluates the effect of non-surgical periodontal therapy (NSPT) on systemic inflammation and glycemic control in patients with T2DM and chronic periodontitis. Objective: To compare the changes in inflammatory biomarkers (IL-6, TNF-α, and CRP) and glycemic control (HbA1c) in T2DM patients and non-diabetic controls after NSPT. Methods: A 3-month prospective cohort study was conducted on 60 patients divided into two groups: Group A (n=30) with T2DM and chronic periodontitis, and Group B (n=30) with chronic periodontitis only. Clinical periodontal parameters (PPD, CAL, BOP), serum inflammatory biomarkers, and HbA1c levels were measured at baseline and 12 weeks after NSPT. Results: Both groups showed significant improvements in periodontal parameters (p < 0.05). Group A exhibited a statistically significant reduction in HbA1c (from 8.1% to 7.4%, p < 0.01), and inflammatory biomarkers decreased markedly in both groups. The magnitude of reduction in IL-6 and CRP was more pronounced in Group A. Conclusion: NSPT improves both periodontal health and systemic inflammation. In T2DM patients, these improvements are accompanied by enhanced glycemic control, underscoring the importance of periodontal care in systemic disease management.